Numerical Optimization and Map-Based Manipulation With a Quadrupole Electromagnetic Actuated System - Ma, Weicheng; Huan, Zhijie; Xu, Min (Frontiers in Neurorobotics, 2022)
Electromagnetic actuation is a new technique for non-invasive manipulation, which provides wireless and controllable power source for magnetic micro/nano particles. This technique shows great potential in the field of precise mechanics, environment protection and biomedical engineering. In this paper, a new quadrupole electromagnetic actuated system is constructed, this system is composed of four electromagnetic coils, each of the coil is actuated by an independent DC power supplier. The magnetic field distribution in the workspace is obtained through finite element modeling and numerical simulation via COMSOL, as well as the effect of the current flow through the coil in the field distribution. Moreover, parameters of the electromagnetic system are optimized through parametric modeling analysis. A magnetic field map is constructed for rapidly solving the desired driving current from the required magnetic flux density. Experiments were conducted to manipulate a microparticle along desired circular path. The proposed work provides theoretical references and numerical fundamental for the control of magnetic particle in future.